IT systems and decisions in business and industry practice selected, peer reviewed papers from the International Conference XXII Mountain School of Association of Information Society, June 22-24, 2015, Czestochowa, Poland - Grabara, Janusz K.; Kot, Sebastian (Applied mechanics and materials, 2015)
Selected, peer reviewed papers from the International Conference XXII MOUNTAIN SCHOOL OF ASSOCIATION OF INFORMATION SOCIETY, June 22-24, 2015, Czestochowa, Poland. The book contains 35 papers and covers a wide range of topics: Information Technology, Information Society, Information Strategy, Computer System and Information Management